Culture of Peace: Conceptions, Perceptions and Commitments (2019)
This book presents the results of the research on peace culture conducted at the Cooperative University of Colombia, Bogotá headquarters. This issue is relevant, while Colombia is listed as one of the most violent countries in the world, which makes its culture vulnerable. The university community is aware that the construction of a culture of peace is a challenge and, at the same time, a premise to achieve the development of society. Its construction demands the participation of all. As part of university social responsibility, it is necessary to know how peace is projected from the university environment. For this, it must be understood what conceptions of peace and culture of peace people have and what commitments they are willing to make to build new processes and social relationships based on respect and empathy. The results of this research are permeated by the humanizing tendency of education, which, motivated the transcending rigid and stiff positions, to assume the participation and personal and collective interest in the creation of a culture of peace. Thus, this document presents relevant reflections and commitments, which are based on the social responsibility that the UCC must fulfill (as well as all universities), in relation to the issue of peace; articulating knowledge, experience, resources, and wills to respond to the challenges demanded by the creation and sustainability of a less violent society.